Rules of thumb for maintenance and reliability engineers - Smith, Ricky (Elsevier/Butterworth-Heinemann, 2008)
Rules of Thumb for Maintenance and Reliability Engineers will give the engineer the “have to have” information. It will help instill knowledge on a daily basis, to do his or her job and to maintain and assure reliable equipment to help reduce costs. This book will be an easy reference for engineers and managers needing immediate solutions to everyday problems. Most civil, mechanical, and electrical engineers will face issues relating to maintenance and reliability, at some point in their jobs